Drying of sodium silicate solutions - Dent Glasser, L. S.; Lee, C. K. (Wiley, 1971)
Sodium silicate solutions with a silicon dioxide:sodium monoxide mole ratio of 3.41:1 were dried gently to give amorphous solids. These solids, together with the products obtained by heating them at various temperatures up to ∼ 200°c, were studied by differential thermal analysis, solubility tests and other techniques. The resultant data give some insight into the structural changes which occur in the solid during the drying process.